2018
DOI: 10.4084/mjhid.2018.043
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of Kaposiform Hemangioendothelioma with long-term sirolimus treatment: a case report and review of the literature

Abstract: BackgroundKaposiform Hemangioendothelioma (KHE) is a rare vascular tumour of the infancy and the first decade of life. It is locally aggressive and potentially life threatening when associated with consumptive coagulopathy, known as Kasabach-Merritt syndrome (KMS). No consensus or guideline for the therapy has been reached because of the lack of prospective trials, and the different standard care suggestions are based on retrospective case series.Case reportWe report the case of a 9-month-old male with KHE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
(40 reference statements)
1
14
0
4
Order By: Relevance
“…Surgical resection is the optimal treatment for KHE among these treatment strategies, in this study, the comparison of the clinical curative effect before and after operation revealed that the clinical curative effect of surgical treatment was great; however, surgery may cause excessive bleeding due to thrombocytopenia, we transfused platelets to those infants with low platelet counts before surgery, which showed remarkable preventive effects on hemorrhage. In addition, the drug therapy for KHE using angiogenesis inhibitor sirolimus targeting the mammalian target of rapamycin (mTOR) [13][14][15] , have been shown to be efficacious. While prednisolone, vincristine and sirolimus showed some effectiveness in decreasing the tumor size 16,17 , can cause side effects such as abdominal pain, elevations of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), opportunistic infection, loss of appetite, etc 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the optimal treatment for KHE among these treatment strategies, in this study, the comparison of the clinical curative effect before and after operation revealed that the clinical curative effect of surgical treatment was great; however, surgery may cause excessive bleeding due to thrombocytopenia, we transfused platelets to those infants with low platelet counts before surgery, which showed remarkable preventive effects on hemorrhage. In addition, the drug therapy for KHE using angiogenesis inhibitor sirolimus targeting the mammalian target of rapamycin (mTOR) [13][14][15] , have been shown to be efficacious. While prednisolone, vincristine and sirolimus showed some effectiveness in decreasing the tumor size 16,17 , can cause side effects such as abdominal pain, elevations of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), opportunistic infection, loss of appetite, etc 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Спроба пункційної біопсії судинної пухлини печінки описана в поодиноких джерелах, більшість авторів вважає цей метод діагностики ризикованим у зв'язку з можливістю виникнення неконтрольованої кровотечі або з провокацією швидкого росту пухлини [8,14,17]. В аналізі 42 літературних джерел за останні роки, що описують поодинокі випадки та невеликі групи пацієнтів із КГЕ вказується, що в 55% випадках біопсія пухлини не проводилась [1]. Важливу роль в діагностиці відіграє імуногістохімічне дослідження, з визначенням маркерів CD-31 та CD-34.…”
Section: клінічний випадокunclassified
“…З 2010 року й по теперішній час проводиться проспективне дослідження щодо ефективності та безпечності використання сіролімусу -інгібітору mTOR рецепторів -для лікування КГЕ [1,3,10,16,23]. Попередні результати цих досліджень у новонароджених є потенційно успішними, але допоки не можуть рахуватися доказовими у зв'язку з малою для статистичної достовірності кількістю пацієнтів.…”
Section: клінічний випадокunclassified
See 1 more Smart Citation
“…KMP occurs in 70% of patients. 11 Although KHE is histopathologically benign, it is locally aggressive and potentially life-threatening when associated with KMP.…”
Section: Locally Aggressive or Borderline Vascular Neoplasms Kaposifomentioning
confidence: 99%